Histone Deacetylase 11 Contributes to Renal Fibrosis by Repressing KLF15 Transcription - Mao, Lei; Liu, Li; Zhang, Tao; Qin, Hao; Wu, Xiaoyan; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Renal fibrosis represents a key pathophysiological process in patients with chronic kidney diseases (CKD) and is typically associated with a poor prognosis. Renal tubular epithelial cells (RTECs), in response to a host of pro-fibrogenic stimuli, can trans-differentiate into myofibroblast-like cells and produce extracellular matrix proteins to promote renal fibrosis. In the present study we investigated the role of histone deacetylase 11 (HDAC11) in this process and the underlying mechanism. We report that expression levels of HDAC11 were up-regulated in the kidneys in several different models of renal fibrosis. HDAC11 was also up-regulated by treatment of Angiotensin II (Ang II) in cultured RTECs. Consistently, pharmaceutical inhibition of a small-molecule inhibitor of HDAC11 (quisinostat) attenuated unilateral ureteral obstruction (UUO) induced renal fibrosis in mice. Similarly, HDAC11 inhibition by quisinostat or HDAC11 depletion by siRNA blocked Ang II induced pro-fibrogenic response in cultured RTECs. Mechanistically, HDAC11 interacted with activator protein 2 (AP-2a) to repress the transcription of Kruppel-like factor 15 (KLF15). In accordance, KLF15 knockdown antagonized the effect of HDAC11 inhibition or depletion and enabled Ang II to promote fibrogenesis in RTECs. Therefore, we data unveil a novel AP-2a-HDAC11-KLF15 axis that contributes to renal fibrosis.